Pemberdayaan Masyarakat dalam Meningkatkan Kepedulian Terhadap Stunting untuk Meningkatkan Derajat Kesehatan Masyarakat Monano - Lanto Mohamad Kamil Amali; Yasin Mohamad; Nova Elysia Ntobuo (Univeristas Negeri Gorontalo, 2022)
Stunting cases in Indonesia are still relatively high, reaching 30.8%. This figure is still far from the WHO standard of 20%. The stunting prevalence rate in North Sulawesi is 25.5%, although the stunting rate in North Sulawesi is below the national figure (30.8%). One part of the community service program is the prevention of stunting that occurs in the community. Because most people do not understand correctly about stunting, and think that stunting or dwarfism is a term commonly used in society is a hereditary factor. This community service activity is carried out to increase knowledge and understanding as well as community participation in the stunting prevention and early detection program in toddlers which is expected to directly motivate the community to participate in paying attention to the growth and development of their children so that their growth and development can be optimal. The method used is lecture, interactive, and question and answer